Folic acid content and fruit characteristics of five Indonesian dessert banana cultivars - RITA NINGSIH; RITA MEGIA (Society for Indonesian Biodiversity, 2019)
Ningsih R, Megia R. 2019. Folic acid content and fruit characteristics of five Indonesian dessert banana cultivars. Biodiversitas 20: 144-151. Folic acid plays an important role in the many metabolic functions of organism, especially pregnant women. Whereas banana is a fruit that rich in nutrients, high productivity, high diversity, well known, and widely consumed in many countries and by various communities from infants to elderly. The research aimed to analyze folic acid content and describe the morphology of mature fruits at three different genomic groups of five Indonesian dessert banana cultivars namely Ambon Kuning (AAA), Ambon Lumut (AAA), Raja Sereh (AAB), Raja Bulu (AAB), and Lampung (AA). The folic acid content of fruit was analyzed using HPLC equipped with a UV-vis detector. Fruit characters were analyzed based on 21 descriptors then subjected to clustering analysis. The result shows that folic acid content of mature stage was 22.26; 21.39; 22.59; 21.2; and 24.58 ?g/100 g fresh weight for those five banana cultivars respectively. Lampung cultivar showed the highest value. Analysis of variance followed by DMRT at 5% probability showed that folic acid, bunch weight, fruit weight, and fruit length were significantly diverse among those five cultivars. Clustering analyses revealed that two groups were formed. The first comprises of Ambon Kuning and Ambon Lumut while the second of Raja Sereh, Lampung, and Raja Bulu. Lampung cultivar was closely related to Raja Sereh than the other cultivars. Adjusted Rand Index analyzed concluded that the immature peel color, mature pulp color, and predominant taste were the best distinctive characters. This knowledge can be used as a consideration for the plant breeding program especially in nutrition improvement.